Alzheimer and vascular brain disease: Senile dementia - Engelhardt,Eliasz (2015)
Alois Alzheimer is best known for his description of a novel disease, subsequently named after him. However, his wide range of interests also included vascular brain diseases. He described Senile dementia, a highly heterogeneous condition, and was able not only to distinguish it from syphilitic brain disease, but also to discriminate two clinicopathological subtypes, that may be labeled a "arteriosclerotic subtype", comparable to the present clinicopathological continuum of "Vascular cognitive impairment", and another as a "neurodegenerative subtype", characterized by primary [cortical] ganglion cell [nerve cells] degeneration, possibly foreshadowing a peculiar presenile disease that he was to describe some years later and would carry his name. He also considered the possibility of a senile presentation of this disease subtype, which was described by Oskar Fischer a short time later. Considering the clinicopathological overlapping features of the "arteriosclerotic subtype" of Senile dementia with Arteriosclerotic atrophy of the brain, it might be possible to consider that both represent a single condition.